Novel Photo- and Thermo-Responsive Nanocomposite Hydrogels Based on Functionalized rGO and Modified SIS/Chitosan Polymers for Localized Treatment of Malignant Cutaneous Melanoma - Céspedes-Valenzuela, Daniela N.; Sánchez-Rentería, Santiago; Cifuentes, Javier; Gómez, Saul C.; Serna, Julian A.; Rueda-Gensini, Laura; Ostos, Carlos; Muñoz-Camargo, Carolina; Cruz, Juan C. (Frontiers in Bioengineering and Biotechnology, 2022)
Melanoma is an aggressive type of skin cancer that accounts for over 75% of skin cancer deaths despite comprising less than 5% of all skin cancers. Despite promising improvements in surgical approaches for melanoma resection, the survival of undetectable microtumor residues has remained a concern. As a result, hyperthermia- and drug-based therapies have grown as attractive techniques to target and treat cancer. In this work, we aim to develop a stimuli-responsive hydrogel based on chitosan methacrylate (ChiMA), porcine small intestine submucosa methacrylate (SISMA), and doxorubicin-functionalized reduced graphene oxide (rGO-DOX) that eliminates microtumor residues from surgically resected melanoma through the coupled effect of NIR light-induced photothermal therapy and heat-induced doxorubicin release. Furthermore, we developed an in silico model to optimize heat and mass transport and evaluate the proposed chemo/photothermal therapy in vitro over melanoma cell cultures.